The Role of Waste Banks in Managing Waste in Kolaka, Southeast Sulawesi Province: Sustainable Environmental Solutions - Siti Nurfadilah H; Mega Sabara; Fivin Ramadani; Hamdawang (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Waste remains a significant environmental challenge in Indonesia, including in Southeast Sulawesi Province. Waste management in the region continues to be inadequate, as evidenced by the increasing volume of waste generation reported annually. This indicates persistent issues in handling and reducing waste effectively. Objective: The objective of this study is to examine the role and impact of waste banks in managing and controlling waste in Kolaka Regency. Method: This study employs an Online Research Method (ORM), in which data collection is conducted via internet sources. The data utilized in this study are secondary data, obtained from previously collected, processed, and published sources, including government statistical agencies and the Central Statistics Agency (BPS). Results: The findings reveal that one of the primary factors contributing to the failure of waste management programs is the low level of public awareness and participation. The lack of community engagement hampers the effectiveness of waste bank initiatives in mitigating environmental pollution. Conclusion: The study concludes that the mere availability of waste banks is insufficient to address the waste problem in Kolaka Regency. Without increased public awareness and active participation in waste management efforts, the goals of environmental sustainability cannot be achieved. Therefore, enhancing public consciousness regarding proper waste disposal and promoting sustainable waste management practices should be prioritized. Keywords: Indonesia, Waste Management, Environmental Pollution, Internet, Government